Action Research in Underserved High Schools: Effective Pedagogy in Music Classrooms - Brummel, Jessica; Davidson, Sidnie; Giles, Abigail; Howard, Addyson; Meek, Alex; Robinson, Abigail (Dept. of Arts and Sciences, 2019)
Given widespread educational crumbling infrastructure, a difference in the quality of education is addressed in the areas of pedagogies, quality of space, amount of resources, and socio emotional support from teachers. In collaboration with students of schools in the KCK area, seniors of the Interior Architecture and Product Design (IAPD) program at Kansas State University, and my research team, we will design a collaborative creative experience utilizing the tenants of Culturally Relevant Pedagogy to create innovative curricular design. The purpose of this study is to identify issues present in underserved schools (Darling-Hammond, 2010) and research pedagogies and classroom design strategies that prove to be both the most effective for student learning and easily implemented in the classroom. The students’ perspectives in this study align most closely with the six tenants of culturally relevant pedagogy. (Ladson-Billings, 1994) These six tenants are divided into two areas; pedagogical and ideological prongs. The three pedagogical prongs are Cultural Competence, Sociopolitical Consciousness, and Academic Achievement. The three ideological prongs are Strong Conception of Self and Others, Teacher’s Strong Conceptions if Social Relationships, and Conceptions of Knowledge. The methodology of our qualitative research study is action research. (Pelton, 2010) This is obtained through our partnership with two high schools, the IAPD department, and professors from the IAPD and Music Education program at Kansas State University. We will interview the students and teachers of those two schools on their educational experiences to discover effective implementation of those 6 tenants listed above. We hope that through this project we will learn how recreate current spaces and curriculums into tools to support student success and inspire other teachers to do likewise, especially in underserved areas of the United States and beyond.
Kirmser Undergraduate Research Award - Group category, honorable mention
Keywords: Action Research; Qualitative Research Study; Kansas City, Kansas; Underserved Schools; Collaborative Creative Experience; Classroom Design Strategies; Culturally-Relevant Pedagogy